Childhood exposure to metal(loid)s in industrial and urban areas along the Persian Gulf using toenail tissue as a biomarker. (15th December 2021) - Parhizkar, Gohar; Khalili Doroodzani, Atefeh; Dobaradaran, Sina; Ramavandi, Bahman; Hashemi, Seyed Enayat; Raeisi, Alireza; Nabipour, Iraj; Keshmiri, Saeed; Darabi, Amirhossein; Afrashte, Sima; Khamisipour, Gholamreza; Keshtkar, Mozhgan
Abstract: Metal(loid)s (MLs) with natural or anthropogenic sources may cause adverse health effects in children. This study aimed to compare the childhood exposure to ΣMLs (essential, non-essential and toxic) in an industrial and an urban area in Southwest Iran using toenail tissue as a biomarker. The present study was carried out with school children in the age range of 7–12 years, who were living in an industrial area in the petrochemical and gas area (PGA) of the Central District of Asaluyeh County and in an urban area (UA) located in the Kaki District. A total of 270 boys and girls were recruited in January to April 2019. The ICP-MS was used for determination of the studied MLs. A multi-linear regression model was constructed to assess the effect of residence area on toenail ML levels. A significantly higher level of ΣMLs in toenail from the PGA was observed compared to the level in the UA (8.839 vs. 7.081 μg/g, β  = -0.169 and p  < 0.05). However, all of the 15 MLs studied were detected in the toenail samples from both study sites. Significant differences for the mean Cr ( β  = −0.563), Fe ( β  = −0.968), Mn ( β  = −0.501), Ni ( β  = −0.306), and Pb ( β  = −0.377) levels were found between toenail samples from the study areas ( p  < 0.05), with higher levels in the PGA. The results of this study suggest that children in industrial area are prone to a greater risk for ML exposures compared with those living in a non-industrial urban area. Graphical abstract: Image 1 Highlights: The level of 15 MLs in toenail samples of school children was studied. A significantly higher level of ΣMLs was found in industrial area than urban area. Al had the highest level of the investigated MLs in toenail tissues. Pb, Ni, Cr, Mn, and Fe levels were significantly higher in industrial area than urban. Abstract : Higher accumulation of metal(loid)s in the toenail of children in an industrial area compared to those in a non-industrial area.